Franco: “Freemasonry is an enemy that never surrenders”: Lázaro Cárdenas, Spain’s refugees and a Franco spy in Mexico - Morales Ruiz, Juan José (2021)
In this article I describe Franco sending a secret agent to the President’s Cárdenas’ Mexico to spy on Spanish republican refugees. My source is a Military Police and Information Service (SIPM) report, which plans as of October 1939, to use an agent settled in Mexico City to infiltrate the Spanish colony and the Republican refugees, destabilize the Mexican electoral campaign  and, above all, monitor the so-called “Spanish gold”, which Negrín and Indalecio Prieto had deposited, with the complicity of the President Cárdenas, at the National Bank of Mexico after fleeing Spain at the end of the Spanish civil war.